Deleted in Breast Cancer 1 regulates cellular senescence during obesity. Issue 5 (3rd July 2014) - Escande, Carlos; Nin, Veronica; Pirtskhalava, Tamar; Chini, Claudia C.; Thereza Barbosa, Maria; Mathison, Angela; Urrutia, Raul; Tchkonia, Tamar; Kirkland, James L.; Chini, Eduardo N.
Summary Chronic obesity leads to inflammation, tissue dysfunction, and cellular senescence. It was proposed that cellular senescence during obesity and aging drives inflammation and dysfunction. Consistent with this, clearance of senescent cells increases healthspan in progeroid mice. Here, we show that the protein Deleted in Breast Cancer‐1 (DBC1) regulates cellular senescence during obesity. Deletion of DBC1 protects preadipocytes against cellular senescence and senescence‐driven inflammation. Furthermore, we show protection against cellular senescence in DBC1 KO mice during obesity. Finally, we found that DBC1 participates in the onset of cellular senescence in response to cell damage by mechanism that involves binding and inhibition of HDAC3. We propose that by regulating HDAC3 activity during cellular damage, DBC1 participates in the fate decision that leads to the establishment of cellular senescence and consequently to inflammation and tissue dysfunction during obesity.